Possibilities of using leaves cultivated chicory (Cichorium intybus L.) as a medicinal plant material (review) - P. O. Mavrina; O. L. Saybel; E. L. Malankina (Овощи России, 2021)
Common chicory (Cichorium intybus L.) is widely known as a food plant. However, in folk medicine in many countries, the roots and leaves of chicory are used as a choleretic, anti-inflammatory, hypoglycemic agent. In this regard, a promising direction of research is a detailed study of the biological characteristics and chemical composition of this plant in order to substantiate its use for therapeutic and prophylactic purposes. The article presents an analysis of the available information on the botanical classification and biological characteristics, agricultural technology, chemical composition and the use of the aerial part of the cultivated common chicory in scientific and folk medicine. Possible resources for collecting chicory leaves are wild-growing populations, as well as varieties of root chicory, which is grown in Russia as an industrial crop. Under natural conditions, chicory occupies disturbed habitats characterized by low soil fertility, pollution with heavy metals, and increased competition with other ruderal plants. While in the conditions of culture, the best agroecological conditions for growing plants are provided, accelerating their development and contributing to accumulation of biologically active substances in greater quantities, compared with wild ones. In this regard, a promising direction of research is to study the influence of various factors (illumination, temperature, weather conditions, agrotechnical measures, varietal characteristics, growth regulators) on the content, qualitative composition and dynamics of the accumulation of biologically active compounds in the leaves of cultivated common chicory.